2020
DOI: 10.1186/s12887-020-02048-2
|View full text |Cite
|
Sign up to set email alerts
|

Etiological serotype and genotype distributions and clinical characteristics of group B streptococcus-inducing invasive disease among infants in South China

Abstract: Background: Group B streptococcus (GBS)-induced invasive disease is a major cause of illness and death among infants aged under 90 days in China; however, invasive GBS infection remains unknown in China. We aimed to describe the serotype and genotype distributions of early-onset disease (EOD) and late-onset disease (LOD), and to show the clinical correlations among various GBS serotypes and genotypes obtained from infants with invasive GBS infections. Methods: Between June 1, 2016 and June 1, 2018, 84 GBS stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…Second, the lack of performing GBS serotyping. Some studies emphasize the importance of serotyping of GBS because it is suggested that GBS has different clinical features depending on its serotype [ 22 , 23 ]. Third is the lack of placental pathology that could have provided evidence to support the relationship between GBS infection and chorioamnionitis and placental membrane inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the lack of performing GBS serotyping. Some studies emphasize the importance of serotyping of GBS because it is suggested that GBS has different clinical features depending on its serotype [ 22 , 23 ]. Third is the lack of placental pathology that could have provided evidence to support the relationship between GBS infection and chorioamnionitis and placental membrane inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that technological barriers to using telemedicine may exacerbate existing health disparities rather than decreasing disparities by increasing access [ 13 , 14 ]. This can lead to intervention-generated inequalities, widening the gap between those who own a device with videoconferencing capability, are comfortable using that technology, and have access to the internet versus those who do not have these resources.…”
Section: Discussionmentioning
confidence: 99%
“…The same people who have access to technology are also likely to be more educated with more social and economic resources, reinforcing the already better health outcomes of this group [15] . In addition, interpreter services may not be as readily available for use in telemedicine, impacting the options available for those with low English proficiency [13] . A third of our patients still came to clinic, demonstrating that it is still important to offer a clinic option for those who have limited technology access, screen in to requiring an ultrasound, or prefer a face-to-face interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The median time to starting an oral diet was 19.3 h in the early feeding group versus 34.7 h in the fasting group. There were no differences between the two groups in terms of the time to discharge, serum amylaste/lipase at discharge, or weight change during admission [ 48 ]. Additional data to support early patient-directed nutrition in children with acute pancreatitis comes from a study by Ellery et al, which compared 30 prospectively recruited patients with acute pancreatitis (ages 2–21) to retrospective data from 92 patients.…”
Section: Pediatric Populationsmentioning
confidence: 99%